Capacity Building in Sub-Saharan Africa as Part of the INTENSE-TBM Project During the COVID-19 Pandemic - Ariza-Vioque, E.; Ello, F.; Andriamamonjisoa, H.; Machault, V.; Gonza´lez-Martın, J.; Calvo-Cortes, M. C.; Eholie, S.; Tchabert, G. A.; Ouassa, T.; Raberahona, M.; Rakotoarivelo, R.; Razafindrakoto, H.; et al. (Infectious Diseases and Therapy, 2022)
Tuberculous meningitis (TBM) is the most severe and disabling form of tuberculosis (TB), with at least 100,000 cases per year and a mortality rate of up to 50% in individuals co-infected with human immunodeficiency virus type 1 (HIV-1). To evaluate the efficacy and safety of an intensified antitubercular regimen and an anti-inflammatory treatment, the INTENSE-TBM project includes a phase III randomised clinical trial (TBM-RCT) in four countries in sub-Saharan Africa (SSA). Within this framework, we designed a comprehensive capacity-building work package ensuring all centres had, or would acquire, the ability to conduct the TBM-RCT and developing a network of skilled researchers, clinical centres and microbiology laboratories. Here, we describe these activities, identify strengths/challenges and share tools adaptable to other projects, particularly inlow-and lower-middle income countries with heterogeneous settings and during the coronavirus disease 2019 (COVID-19) pandemic. Despite major challenges, TBM-RCT initiation was achieved in all sites, promoting enhanced local healthcare systems and encouraging further clinical research in SSA. In terms of certified trainings, the achievement levels were 95% (124/131) for good clinical practice, 91% (39/43) for good clinical laboratory practice and 91% (48/53) for infection prevention and control. Platform-based research, developed as part of capacity-building activities for specific projects, may be a valuable tool in fighting future infectious diseases and in developing high-level research in Africa.
Keywords: Africa; Capacity building; Clinical research; HIV; INTENSE-TBM; Tuberculous meningitis